1936
DOI: 10.1002/j.1537-2197.1936.tb09017.x
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation in Tradescantia

Abstract: life cycle, except for an occasional case of nondisjunction at meiosis.The meiotic behavior of the chromosomes was studied in 100 cells from plants having only one pair of fragments. These data are summarized below and in the following paragraphs. '.92 noo 8.00 Fragments none Normal bivalents 2.4 23.44 Average chiasma frequency . (Ic, of interstitial chiasmata . % unpaired .AMONG A group of Tradescantia 2 plants collected from Gentilly, Louisiana, by Small, Anderson and Woodson, there appeared a number of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1939
1939
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Consequently, the terms 'B chromosome(s)' and 'Bs' are used in the present paper. Also in Tradescantia paludosa supernumerary chromosomes were not found to pair with standard chromosomes at MI [Whitaker, 1936]. In many studies it was shown that despite their univalency Bs have the capacity to pass though meiosis and to be still maintained in populations [Jones and Rees, 1982;Jones, 1995].…”
Section: Chromosome Counts In Meiosis and Mitosis General Karyotype mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the terms 'B chromosome(s)' and 'Bs' are used in the present paper. Also in Tradescantia paludosa supernumerary chromosomes were not found to pair with standard chromosomes at MI [Whitaker, 1936]. In many studies it was shown that despite their univalency Bs have the capacity to pass though meiosis and to be still maintained in populations [Jones and Rees, 1982;Jones, 1995].…”
Section: Chromosome Counts In Meiosis and Mitosis General Karyotype mentioning
confidence: 99%
“…Mitotic/meiotic propagation of such an amalgamate of sequences seems possible by recruiting centromere DNA and/or generating epigenetic effects enabling spindle microtubule attachments, and/or by adding telomeric motifs stabilizing the ends of a newly arisen B chromosome [Dhar et al, 2002;Jones and Houben, 2003]. Previous models on the origin of supernumerary chromosomes in Tradescantia suggested fragmentation of a major portion of an A chromosome with the preservation of its original centromeric region, which then could act as a donor functional domain [Whitaker, 1936;Swanson, 1943]. However, the structural similarity of Bs and distal chromosome regions indicates quite a different route of B chromosome escape in T. virginiana .…”
Section: Distal Regions Of a Chromosomes Share A Similar Cytomoleculamentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the hypothesis suggested by Whitaker (1936) in an attempt to explain the pairing of extra diminutives in Tradescantia will apply also to Oenothera. Whitaker has evidence to show that the pairing extras in Tradescantia paludosa are fragments which represent median segments of a normal chromosome.…”
Section: Origin Of Diminutivesmentioning
confidence: 99%
“…According to the mutation accumulation theory of aging (Medawar 1952), organisms senesce because their machinery is unable to reverse deleterious mutations at a rate higher than the rate at which they occur. The plant ecophysiological literature is mined with examples of species that can compartmentalize risk such as cavitation, fungal attacks and other diseases (Orians et al 2005;Casper 2010, 2011;Schenk 1999;Schenk et al 2008;Whitaker 1946;Zanne et al 2006). Plant clonality, whereby modules (i.e.…”
Section: Introductionmentioning
confidence: 99%